До теорії систем: швидкий огляд особливостей понять в концептуальному полі - Kolyada, Vladimir P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
From the systems theory point of view the attempting was made to establish the most suitable logical and semantical conceptual definition for systems notions while maintaining the maximal compatibility in the theoretical field, which enable to bring together systems with any scale and complexity to a single strategy of interpretation of their dynamics. The special semantic clarifications for notions which generating theoretical ground were established. Thus specified fundamental and system-forming processes. Direct relations of specific terms and subtleties of differences of system notions, their roles for creating solid theoretical representation were highlighted. Some examples of the biochemical types are given. An explicit, semantic clarification of some concepts describing the dynamics of systems and states is proposed.